Integrated care for HIV/AIDS infected patients. The Romanian experience - Miruna-Maria Apetroaei; Marina Ionela Ilie; Andreea Letitia Arsene (Romanian Journal of Pharmaceutical Practice, 2022)
The human immunodeficiency virus (HIV) targets the body’s immune system and, if left untreated, may result in acquired immunodeficiency syndrome. (AIDS). HIV’s pathogenesis entails the gradual destruction of CD4+ T cells, which lowers the immune system and leaves the body more susceptible to co-infections and other diseases. HIV has been highlighted as a global public health concern, and since the first instances were recorded in the early 1980s, it has caused extensive morbidity and mortality. The HIV epidemic is still impacting millions of individuals throughout the entire globe, even though available antiretroviral therapy (ART) has transformed HIV infection from an almost universally fatal disease into a controllable chronic medical condition. The magnitude of the HIV epidemic varies between areas and countries. In 2021, the Joint United Nations Program on HIV/AIDS (UNAIDS) projected that 38.4 million individuals worldwide were living with HIV. The HIV integrated care approach highlights the significance of early diagnosis, care coordination, and medication adherence. This strategy incorporates a multidisciplinary team of medical specialists, including physicians, pharmacists, social workers, nurses, and mental health professionals. In addition to medication management, mental health counseling, drug addiction treatment, and peer support, HIV-integrated care includes additional therapies such as behavioral health counseling. HIV integrative care is a holistic approach to HIV infection management that addresses patients’ medical, interpersonal, and emotional requirements. It has been demonstrated that this form of treatment improves health outcomes, reduces stigma, and increases community involvement in combating HIV infections.